2018
DOI: 10.1007/s00787-018-1177-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term neurodevelopmental consequences of intrauterine exposure to lithium and antipsychotics: a systematic review and meta-analysis

Abstract: Lithium and antipsychotics are often prescribed to treat bipolar disorder or psychotic disorders in women of childbearing age. Little is known about the consequences of these medications during pregnancy for the developing child. The objective of this article is to systematically review findings from preclinical and clinical studies that have examined the neurodevelopmental consequences of intrauterine exposure to lithium and antipsychotics. A systematic search was performed in Embase, Medline, Web of Science,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 114 publications
(137 reference statements)
1
28
0
1
Order By: Relevance
“…Effects of prenatal antipsychotic use during pregnancy on autism risk are largely unknown, due to a paucity of relevant quality data [262, 263]; one study [264] reported increased head circumference, an autism-associated trait, in neonates prenatally exposed to the antipsychotics olanzapine and/or clozapine, but birth weight and length, which are also commonly higher in autism, were not affected.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of prenatal antipsychotic use during pregnancy on autism risk are largely unknown, due to a paucity of relevant quality data [262, 263]; one study [264] reported increased head circumference, an autism-associated trait, in neonates prenatally exposed to the antipsychotics olanzapine and/or clozapine, but birth weight and length, which are also commonly higher in autism, were not affected.…”
Section: Resultsmentioning
confidence: 99%
“…Aside from lithium teratogenicity, neonatal toxicity events may occur in offspring exposed to lithium during labor, including the so-called floppy baby syndrome (characterized by cyanosis and hypotonicity), neonatal hypothyroidism, and nephrogenic diabetes insipidus (9). Nonetheless, the appraisal of the risk for long-term adverse neurodevelopmental consequences of intrauterine exposure to lithium is hampered by the fact that most studies have compared exposed children with children from unaffected populations, which did not allow for correction of the potential influence of genetic predisposition or parental psychiatric illness (10).…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal exposure to lithium may therefore have consequences on development and health outcomes well beyond infancy. Indeed, results from preclinical studies in mice, rats and zebrafish show neurodevelopmental deficits (Poels et al 2018). Clinical data are scarce, four small clinical cohort studies have investigated long term neurodevelopmental outcomes.…”
Section: Consequences For the Developing Childmentioning
confidence: 99%